Preferred technique of creating pneumoperitoneum for laparoscopy by pediatric surgeons - Amar A. Shah; Anirudh V. Shah (SpringerOpen, 2022)
Abstract Background Minimally invasive pediatric surgery has gained popularity over open conventional surgery as it offers benefits to both patients and health care practitioners. Creation of pneumoperitoneum is a must for any laparoscopic procedure. Different pediatric surgeons have their individual preferences regarding the technique to create pneumoperitoneum prior to laparoscopy. The aim of this study was to evaluate the preference of technique for the creation of pneumoperitoneum in pediatric laparoscopy among Indian Pediatric Surgeons. The study was designed by communication with members of the Indian Association of Pediatric Surgeons using a predefined questionnaire. 180 pediatric surgeons responded to the survey. The respondents included pediatric surgeons in institutional and private practice. The reasons behind their preference were enumerated and evaluated. Results Seventy-one percent of pediatric surgeons preferred the primary open technique for the creation of pneumoperitoneum. Seventeen percent exclusively used Veress needle whereas 12% were using both techniques varying from patient to patient. Conclusion Creation of pneumoperitoneum remains an important safety issue for all pediatric surgeons. Pediatric Surgeons in India prefer using the primary open technique for the creation of pneumoperitoneum for laparoscopic surgery.